IMPLEMENTATION OF DESIGN THINKING SIAKAD MOBILE DESIGN WITH ADVANCED SUS ANALYSIS - Elydiya Yahya, Diva; Muqtadir, Asfan; Nurlifa, Alfian (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2026)
Abstract: The development of information technology has begun to enter the world of education, especially universities, one of which is the academic information system because with this system it greatly influences the learning process and also in the delivery of information. A web-based academic information system is very adequate, but there are several obstacles such as in learning that does not require a laptop device, it will be very disruptive if the implementation of attendance and others is done on a mobile phone but with a web view. So this research aims to design a mobile-based UI/UX academic information system application with the hope that it can be an alternative in accessing the use of academic information systems for lecturers and students can also be accessed anytime and anywhere through mobile phones with a comfortable display. This study also tested the UI/UX design prototype to assess its feasibility. This test uses the system usability scale (SUS) method with a convident interval validation of 95% to determine the lower and upper limits of the SUS value. For the final score of SUS obtained was 78.75, and in the 95% CI test a Lower CI of 66.27 was produced, and for the Upper CI of 91.23 so that it was given a grade of B. It can be concluded that the design developed in this study is worthy of further development. Keywords: academic information systems; design thinking; system usability scale Abstrak: Perkembangan teknologi informasi sudah mulai masuk kedalam dunia pendidikan terutama perguruan tinggi, salah satunya sistem informasi akademik karena dengan adanya sistem ini sangat mempengarusi proses pembelajaran dan juga dalam penyampaian informasi. Sistem informasi akademik berbasis web sudah sangat memadai namun ada beberapa kendala seperti dalam pembelajaran yang tidak memerlukan perangkat laptop akan sangat menganggu jika pelaksanaan absensi dan lainya dilakukan pada ponsel tapi dengan tampilan web. Sehingga penelitian ini bertujuan untuk merancang UI/UX aplikasi sistem informasi akademik berbasis mobile dengan harapan dapat menjadi alternatif dalam akses penggunaan sistem informasi akademik bagi dosen dan mahasiswa juga dapat diakses kapan saja dan dimana saja melalui ponsel dengan tampilan yang nyaman. Penelitian ini juga melakukan pengujian terhadap prototype desain UI/UX untuk menilai kelayakannya. Pengujian ini menggunaka metode system usability scale (SUS) dengan validasi convident interval 95% untuk mengetahui batas bawah dan batas atas nilai SUS. Untuk nilai akhir SUS yang didapatkan adalah 78,75, dan dalam pengujian CI 95 % dihasilkan CI Lower 66,27, dan untuk CI Upper 91,23 Sehingga mendapat grade B. Dapat disumpulkan bahwa desain yang dikembangkan dalam penelitian ini layak untuk dikembangkan lebih lanjut. Kata kunci: sistem informasi akademik; desain thinking; system usability scale